2014
DOI: 10.4094/chnr.2014.20.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Simulation Integrated with Problem Based Learning on Clinical Competency and Self-efficacy in Nursing Students.

Abstract: PURPOSE: This study was conducted to examine the effects of simulation education integrated with problem based learning (SIM-PBL) on clinical competency and self-efficacy in post operation nursing care for children.METHODS: This study was a quasi-experimental design. Thirty six students in the third year of a 4-year baccalaureate nursing program were recruited conveniently and assigned to the control or intervention groups using time difference.Students were all in a pediatric nursing clinical practicum.The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…In this study, we found that the neonatal nursing practice program was also effective for improving students' self-efficacy, as general self-efficacy, academic self-efficacy, and social self-efficacy all improved after the program. Self-efficacy is formed by actual or indirect experiences, praise, and encouragement, and is influenced by observing the success of someone similar to oneself [23]. In this study, students' self-efficacy was formed by the experience of performing neonatal physical assessments and basic nursing skills on dummy infants, and it was improved by getting compliments on what they did well during the debriefing, as well as by observing the successful practice of other students if the students had any elements that were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the neonatal nursing practice program was also effective for improving students' self-efficacy, as general self-efficacy, academic self-efficacy, and social self-efficacy all improved after the program. Self-efficacy is formed by actual or indirect experiences, praise, and encouragement, and is influenced by observing the success of someone similar to oneself [23]. In this study, students' self-efficacy was formed by the experience of performing neonatal physical assessments and basic nursing skills on dummy infants, and it was improved by getting compliments on what they did well during the debriefing, as well as by observing the successful practice of other students if the students had any elements that were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the nursing students' perceived self-efficacy in relation to the nursing process of treating patients with cardiac arrest, as well as completing basic CPR and defibrillation, the research team amended and adapted the evaluation tool for nursing process application presented by Kim et al, 33 the self-efficacy tool for nursing students developed by Lee et al, 34 and the standard evaluation items on basic CPR and defibrillation developed by KABONE. 23 The suitability of the items and validity of the content were verified by two professors of basic nursing and two professors of adult nursing.…”
Section: Measures Self-efficacymentioning
confidence: 99%
“…Previous studies have reported on the positive effects of simulation education on nursing and other students' confidence, decision-making ability, communication skills and clinical judgment [2,13e15]; clinical knowledge and performance [16,17]; and self-efficacy or self-confidence, as well as ability to manage anxiety and stress [18]. Insofar as VR simulation is a new learning method, however, the literature around it is limited [5].…”
Section: Introductionmentioning
confidence: 99%